Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Answer:
f(g(-64)) = -190
Step-by-step explanation:
The functions are not well written.
Let us assume;
f(x) = x+1
g(x) = 3x+1
f(g(x)) = f(3x+1)
Replace x with 3x+1 in f(x)
f(g(x)) = (3x+1) + 1
f(g(x)) = 3x + 2
f(g(-64)) = 3(-64) + 2
f(g(-64)) = -192+2
f(g(-64)) = -190
Note that the functions are assumed but same method can be employed when calculating composite functions
Using composite functions, it is found that:
- [tex](f \circ g)(-64) = -8[/tex]
The composite function of functions f(x) and g(x) is given by:
[tex](f \circ g)(x) = f(g(x))[/tex]
Researching the problem on the internet, it is found that the functions are:
[tex]f(x) = (x + 1)^3[/tex]
[tex]g(x) = \sqrt[3]{x} + 1[/tex]
Then, the composite function is:
[tex](f \circ g)(x) = f(g(x)) = f(\sqrt[3]{x} + 1) = (\sqrt[3]{x} + 1 + 1)^3 = (\sqrt[3]{x} + 2)^3[/tex]
At x = -64, we have that:
[tex](f \circ g)(-64) = (\sqrt[3]{-64} + 2)^3 = (-4 + 2)^3 = (-2)^3 = -8[/tex]
Hence:
- [tex](f \circ g)(-64) = -8[/tex]
To learn more about composite functions, you can take a look at https://brainly.com/question/17684028
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.